THE IMPACTS FOR DEVELOPING THE PROFESSION OF SOCIAL WORK IN THE POST-COMMUNIST CONTEXT - Vaike Raudava (European Scientific Journal, ESJ, 2013)
﻿Historical impacts and inconsistency have influenced the development of the field of profession of social work. Independent social caregiver or social worker positions did not exist in the local governments earlier in history since 1995. Today, the profession of the social worker is not specified at the local government level, the ambivalence position of the employer of the social work field: at the client level is existing to the political decision making process and some time the social worker is not included in the decision of social policy in local government. The decision-making process regarding the clients is distributed among different levels, the practice undermines the independence of the social worker and the social worker cannot protect the client. The principle of collective responsibility lives on in the 21st century without giving the profession of social work the opportunity to grow independent.